The Church of England and the First World War - Wilkinson, Alan (The Lutterworth Press, 2014)
"Explores in depth the role of the church during the tragic circumstances of the First World War using biographies, newspapers, magazines, letters, poetry, and other sources in a balanced evaluation." -- back cover